Nudos - Farah, Nuruddin, 1945-; Vázquez Nacarino, Eugenia; Farah, Nuruddin, 1945- (Madrid : Siruela, 2013)
Set in Mogadiscio, Somalia, this novel breaks new ground and brings the author back to his literary roots. He presents the story of a woman raised in North America who returns to her homeland in a desperate attempt to find herself and reclaim her family's home from the warlord who has taken it.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Americans -- Somalia -- Fiction; Mogadishu (Somalia) -- Fiction; Real property -- Somalia -- Fiction; Electronic books